2020
DOI: 10.1101/2020.12.09.417519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal dynamics of intra-host variability in SARS-CoV-2 genomes

Abstract: Since its zoonotic transmission in the human host, the SARS-CoV-2 virus has infected millions and has diversified extensively. A hallmark feature of viral system survival is their continuous evolution and adaptation within the host. RNA editing via APOBEC and ADAR family of enzymes has been recently implicated as the major driver of intra-host variability of the SARS-CoV-2 genomes. Analysis of the intra-host single-nucleotide variations (iSNVs) in SARS-CoV-2 genomes at spatio-temporal scales can provide insigh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 81 publications
3
9
0
Order By: Relevance
“…Mutational surveys of published SARS-CoV-2 genomes reveal overrepresentations of nucleotide changes bearing the signature of RNA editing: adenosine-to-inosine (A-G) changes from ADAR deaminases and cytosine-to-uracil (C-U) changes from APOBEC deaminases (21)(22)(23)(24). The role of APOBEC and ADAR proteins in host innate immunity and their viral directed activities raises the possibility of host immunity contributing to the intra-host heterogeneity observed in the SARS-CoV-2 genome (22,(24)(25)(26). Indeed, this has been proposed as the underlying mechanism for the D614G mutation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational surveys of published SARS-CoV-2 genomes reveal overrepresentations of nucleotide changes bearing the signature of RNA editing: adenosine-to-inosine (A-G) changes from ADAR deaminases and cytosine-to-uracil (C-U) changes from APOBEC deaminases (21)(22)(23)(24). The role of APOBEC and ADAR proteins in host innate immunity and their viral directed activities raises the possibility of host immunity contributing to the intra-host heterogeneity observed in the SARS-CoV-2 genome (22,(24)(25)(26). Indeed, this has been proposed as the underlying mechanism for the D614G mutation (27).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we compared iSNVs and mutation features of SARS‐CoV‐2 VOCs during different stages of COIVD‐19 pandemic. Compared with the previous studies, 11,16,17,30 some interesting findings were obtained, which may deepen our understanding of the adaptive evolution of SARS‐CoV‐2 VOCs, especially Omicron variant. The distribution of iSNVs (Figure 1A–F) showed that VOCs have more iSNVs than the ancestral lineage.…”
Section: Discussionmentioning
confidence: 78%
“…Some of these intra‐host mutations have a positive impact on the virological function 10 . After a period of time, these positive minor mutations can change into the major mutations by competing with other strains 11,12 . Thus, the intra‐host diversity of RNA virus is usually looked as a key marker for understanding the adaptive evolution of the viruses within the host, 13,14 and it is often characterized by intra‐host single‐nucleotide variations (iSNVs) or minor alleles 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the exceptional level of quality control involved in the generation of our sequences in the clinical context, we found that unavoidable technical artefacts, in particular batch effects and the clear effect of RNA input quantity on minor variant calling—even when limiting samples to those with high coverage across the genome—hampered the ability to draw definitive conclusions in the absence of technical replicates and required us to limit our analyses to high input samples. Our results demonstrate that caution is required when, for example, analyzing minor variants from sequence data repositories 36,37 . Rates of different types of error may meaningfully differ between batches of samples such as sequencing runs, between laboratory protocols and even due to factors such as whether individual tubes or plates were used in library preparation 38,39 .…”
Section: Discussionmentioning
confidence: 81%